Molecular Mechanisms of Neurogenic Aging in the Adult Mouse Subventricular Zone - Giuseppe Lupo; Roberta Gioia; Paola Serena Nisi; Stefano Biagioni; Emanuele Cacci (Journal of Experimental Neuroscience, 2019)
In the adult rodent brain, the continuous production of new neurons by neural stem/progenitor cells (NSPCs) residing in specialized neurogenic niches and their subsequent integration into pre-existing cerebral circuitries supports odour discrimination, spatial learning, and contextual memory capabilities. Aging is recognized as the most potent negative regulator of adult neurogenesis. The neurogenic process markedly declines in the aged brain, due to the reduction of the NSPC pool and the functional impairment of the remaining NSPCs. This decline has been linked to the progressive cognitive deficits of elderly individuals and it may also be involved in the onset/progression of neurological disorders. Since the human lifespan has been dramatically extended, the incidence of age-associated neuropsychiatric conditions in the human population has increased. This has prompted efforts to shed light on the mechanisms underpinning the age-related decline of adult neurogenesis, whose knowledge may foster therapeutic approaches to prevent or delay cognitive alterations in elderly patients. In this review, we summarize recent progress in elucidating the molecular causes of neurogenic aging in the most abundant NSPC niche of the adult mouse brain: the subventricular zone (SVZ). We discuss the age-associated changes occurring both in the intrinsic NSPC molecular networks and in the extrinsic signalling pathways acting in the complex environment of the SVZ niche, and how all these changes may steer young NSPCs towards an aged phenotype.